Maler am Bauhaus - Roters, Eberhard (Berlin : Rembrandt Verlag, 1965)
Gropius, Walter ; Feininger, Lyonel ; Itten, Johannes ; Muche, Georg ; Schreyer, Lothar ; Schlemmer, Oskar ; Klee, Paul ; Kandinsky, Wassily ; Moholy-Nagy, Laszlo ; Bayer, Herbert ; Albers, Josef
Duits
boek